Recent advances in the extraction of bioactive compounds from plant matrices and their use as potential antioxidants for vegetable oils enrichment - Oubannin, Samira; Bijla, Laila; Nid Ahmed, Moussa; Ibourki, Mohamed; El Kharrassi, Youssef; Devkota, Krishna; Bouyahya, Abdelhakim; Maggi, Filippo; Caprioli, Giovanni; Sakar, El Hassan; Gharby, Said (Elsevier, 2024)
Oxidation of vegetable oils is a phenomenon that alters the nutritional value of the oil and produces unpleasant flavors, it is also the main factor limiting the quality of vegetable oils during storage. Synthetic antioxidants (SA) are known for their performance to improve vegetable oil oxidative stability. However, owing to their harmful effects on human health, the edible oil industry is seeking safe and healthy natural antioxidants. Indeed, such natural antioxidants, recovered from different plant matrices, demonstrate a potential effect, even better than SA in some cases, to preserve oils from oxidation and to satisfy consumer demand for natural foods. The enrichment of these oils using antioxidants from natural sources is proposed as a solution. Starting with a literature search using “enrich”, “oxidation”, “shelf-life”, “extract”, “antioxidant”, and “aromatic and medicinal plant” as keywords, the present paper provides a detailed overview of all extraction techniques for bioactive compounds and possible methods for enriching vegetable oil mentioning the advantages and drawbacks of each one.